Cesarean Scar Endometriosis: An Uncommon Surgical Complication on the Rise? Case Report and Literature Review - Imane Khachani; Abdelhai Filali Adib; Rachid Bezad (Case Reports in Obstetrics and Gynecology)
Endometriosis is defined by the presence and growth of ectopic functional endometrial tissue outside the uterus. Scar endometriosis has been described following obstetrical and gynecological surgery. It is a rare condition, though probably on the rise, due to the considerable increase of cesarean sections performed worldwide. Its physiopathology is complex; its symptomatology is rich and diverse but thorough clinical examination along with ultrasound imaging and potentially pretherapeutic cytologic evaluation are usually efficient in diagnosing the condition. Treatment is mostly surgical. We report the case of a cesarean section scar endometriosis, managed at a tertiary level center and emphasize the diagnosis and treatment options.